Identification of Sea Surface Temperature Anomaly during Earthquake in Southern Java Island using Google Earth Engine Datasets - Alfi Nur Rusydi; Ferryati Masitoh (Indonesian Journal of Geography, 2023)
The certainty of Sea Surface Temperature (SST) anomaly during earthquakes in Java Island was still not clear identified. This research tried to identify any possibilities of SST anomaly during earthquake in Southern Java Island. It used Google Earth Engine datasets including daily NOAA Climate Data Record (CDR) - Woods Hole Oceanographic Institution (WHOI): Sea Surface Temperature Version 2 which has resolution of 0.25 arc degrees for 20 years and processed them to depict SST trends in pre-earthquake and post-earthquake situation. The statistic test of t-Test Paired Two Sample was also applied to certain the significant difference of SST in both situations. SST fluctuation during the earthquake was still inconsistent and unclear to consider as an anomaly. There were other complicated factors excluding earthquake to influence SST fluctuation. The earthquake did not trigger directly to fluctuate SST, even not to make it being an anomaly.